2012
DOI: 10.1002/chem.201103289
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Dynamic Solution Behavior of Cationic, Two‐Coordinate Gold(I)–π‐Allene Complexes

Abstract: A family of seven cationic gold complexes that contain both an alkyl substituted π-allene ligand and an electron-rich, sterically hindered supporting ligand was isolated in >90% yield and characterized by spectroscopy and, in three cases, by X-ray crystallography. Solution-phase and solid-state analysis of these complexes established preferential binding of gold to the less substituted C=C bond of the allene and to the allene π face trans to the substituent on the uncomplexed allenyl C=C bond. Kinetic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 104 publications
4
39
0
Order By: Relevance
“…Gold( i ) forms stable monomeric two coordinate π-complexes with alkenes, 2022 1,3-dienes, 23 allenes, 24 and substituted alkynes. 19a,25,26 Variations of the bond lengths as well as the ligand–metal-substrate angle suggest that the alkene orientation is controlled largely by steric factors.…”
Section: Activation Of Unsaturated Substratesmentioning
confidence: 99%
“…Gold( i ) forms stable monomeric two coordinate π-complexes with alkenes, 2022 1,3-dienes, 23 allenes, 24 and substituted alkynes. 19a,25,26 Variations of the bond lengths as well as the ligand–metal-substrate angle suggest that the alkene orientation is controlled largely by steric factors.…”
Section: Activation Of Unsaturated Substratesmentioning
confidence: 99%
“…4a, have been developed [27], as such species are crucial in many catalytic applications of gold [28]. X-ray crystal structure determination shows the π-allene ligand to be coordinated at the least congested side (Fig.…”
Section: Intra-molecular Au…π(arene) Interactionsmentioning
confidence: 99%
“…As expected, hydrogen bond acceptors with lower gold affinity (e.g., DMPU, DMF) [141][142][143][144][145][146][147][148] enhanced the rate of reaction (Scheme 14b), and ionic hydrogen bond acceptors (e.g., Bu4N Other research groups reported that certain compounds improved the chemical yields in selected gold catalyzed reactions. 153,154 One notable example is the …”
Section: Scheme 14 Additive Effects On Various Gold Catalyzed Reactisupporting
confidence: 64%